Zinc Electroplating-Hull Cell Studies (Biological Sciences - PJSIR, 2007)
I nfl u ence of addi tives i n acid zi nc chloride plati n g bath was observed. Ei ght various t ypes of additi ves were u sed and effect was studied usi ng H ull cell test. The zi nc plati ng was carried out usi ng bath , zi nc ch loride 50-60 g/1, boric acid 20 g/1, pota ssi um chloride 250-275 g/ 1, at pH 5.0-5.4, temperature 35-40 °C, cel l voltage 1 -1 .1 V, cell current 1 .5 A and platin g d uration five mi nutes. A ppearance of the deposit was best at van il l i n 2.5 g/ 1.